Les risques d’exclusion dans un contexte de transformation organisationnelle - Pierre Pavageau; Adelaide Nascimento; Pierre Falzon (Perspectives Interdisciplinaires sur le Travail et la Santé)
Our research was conducted within two organizations pertaining to the MINEFI (French Ministry of Economics and Budget) around two theoretical concepts: a 3-dimensional model of health and the notion of enabling environment. Organizational changes related to the development of computerization are presented beforehand as a source of difficulty. However, the different analyses yield a different picture: the situation has stabilized, advancing age does not appear to be a major exclusion factor, and the implementation of new technologies is finally positively experienced. Many operators frequently mention enhanced tasks. Beyond change, we feel that the adaptation processes should be the subject of particular attention.